A novel fluorescent chemosensor based on tetra-peptides for detecting zinc ions in aqueous solutions and live cells. Issue 26 (15th June 2016) - Wang, Peng; Wu, Jiang; Su, Pingru; Shan, Changfu; Zhou, Panpan; Ge, Yushu; Liu, Dan; Liu, Weisheng; Tang, Yu
Abstract : A novel fluorescent chemosensor (HL ) based on tetra-peptides conjugated with dansyl groups has been designed and synthesized, which is a promising analytical tool for detecting Zn 2+ in aqueous solutions and live cells. Abstract : A fluorescent chemosensor is a powerful analytical tool for the visualization and quantitation of analytes in living cells, tissue slices, and whole bodies. Peptides with a reporter ionophore are very valuable as fluorescent chemosensors, because of their higher biological compatibility and solubility compared to organic dyes, and they are more stable than proteins in aqueous solutions. Herein, we report a novel peptide fluorescent chemosensor (HL ) based on tetra-peptides conjugated with dansyl groups, which was synthesized by solid phase peptide synthesis. This chemosensor selectively and sensitively detects Zn 2+ based on the photo-induced electron transfer (PET) effect by turn-on response in 100% aqueous solutions. As designed, HL can penetrate live HeLa cells and image intracellular Zn 2+ by turn-on response. Moreover, HL exhibits low biotoxicity with a limit of detection (LOD) of about 32 nM for Zn 2+, implying thatHL acts as a highly useful peptide fluorescent chemosensor for biological systems.